A case of vaginal hyperplasia occurred the last trimester of pregnancy in a Kangal bitch - Safak, Tarik; Yilmaz, Oznur; Ercan, Kerem; Yuksel, Burak Fatih; Ocal, Halis (Ankara Univ Press, 2021)
Vaginal hyperplasia is characterized clinically as the protrusion of edematous hyperplastic mucosa tissue through the vulvar lips. Generally, it is formed during the proestrus and estrus periods in dogs. In this case report, 12 months old, pregnant Kangal breed dog with a mass in the vagina was presented with pre and postoperative findings. The bitch without any genital problems at pro/estrus stages was mated about two months ago. During the clinical examination, it was detected that bitch was in the second stage of labor and had type III vaginal hyperplasia. After the delivery of nine puppies without complication, the bitch was placed under general anesthesia and the hyperplasic tissue was removed surgically. Although no hyperplasia history at pro/estrus stages of the bitch, the fact that vaginal hyperplasia was observed in the last trimester of pregnancy is remarkable. Interestingly, this hyperplastic mass did not cause dystocia during all the puppies' delivery in this case. In conclusion, in pregnant dogs, routine genital exams should be performed once at least until parturition to control vaginal structural integrity.
Kangal ırkı bir köpekte gebeliğin son trimesterinde meydana gelen bir vajinal hiperplazi olgusu
Keywords: Bitch; pregnancy; vaginal hyperplasia